“ANALISIS KINERJA ISLAMIC HUMAN RESOURCES” BERDASARKAN METODE MASLAHAH SCORECARD (STUDI KASUS PADA PT. INALUM) - Sundari, Dewi (Universitas Islam Negeri Sumatera Utara, 2019)
This study discusses the effectiveness of performance based on the Maslahah Scorecard measurement method and reveals the influence of aspects of Maqasid Al-Syariah on the performance of Muslim employees of PT. INALUM. The population in this study were Muslim employees who worked at PT. INALUM which amounted to 1622 employees with a total sample of 94 people responded and then in determining and selecting a sample of researchers using the Convenience Sampling technique. ased on the approach of this study using the Mix Method method. Based on the results of the study it can be concluded that aspects of Maqasid Al-Sharia have a positive and significant effect of 80.8% on performance while the remaining 19.2% is influenced by variables outside of this study and based on statistical calculations that the performance of Muslim employees PT. INALUM has a performance with an effective category with a performance score of 89.9%.